Persepsi Nelayan Tradisional Tentang Nilai Non-Pasar dan Non-Penggunaan Sumberdaya Terumbu Karang di Teluk Doreri Kabupaten Manokwari - Nur Widiastuti; Thomas Frans Pattiasina (Faculty of Agriculture Musamus University, 2022)
Abstract Fishermen who live on the coast of Doreri Bay are the main stakeholders in the management of coral reef ecosystems in the area. Therefore, sustainable coral reef management requires their participation and support. This study aims to determine the perceptions of traditional fishermen about non-market value and non-use value, as well as the main threats to coral reef resources. The research was conducted in October-November 2018. A total of 70 traditional fishermen from 15 villages on the coast of Doreri Bay were selected as respondents. Data processing is done by tabulation method, namely the compilation of data into a formal pattern that has been designed. The results of data processing were then analyzed with a quantitative approach. The results show that traditional fishermen in Doreri Bay have a good understanding of the non-market value and non-use value of coral reef resources. Fishermen also view that the main threats to the preservation of coral reef resources are waste and garbage, as well as the use of destructive fishing gear. Despite having a good understanding of the importance of coral reef resources, compliance with the rules in protecting the environment is still low. Therefore, efforts are needed to develop, supervise, enforce rules/laws, and alternatively improve the family economy.